Dopamine-Conjugated Methacrylated Gelatin Hydrogel—Physical, Mechanical, and Biological Properties - Weiwen Lu; Maedeh Rahimnejad; Beatriz Ometto Sahadi; Marco C. Bottino (Gels, 2025)
This study develops and characterizes GelMA–dopamine conjugates as novel tissue adhesives, offering an alternative to sutures. GelMA was synthesized at 5%, 10%, and 15% (w/v) with medium and high dopamine (DOPA) conjugation. Adhesives were evaluated for swelling, degradation, mechanical strength, and cytocompatibility using AlamarBlue assays and F-actin staining to assess cell viability and adhesion. Our findings indicate that DOPA conjugation significantly reduced the swelling ratio while increasing the biodegradation rate, resulting in enhanced release of free methacrylate groups over time. The mechanical properties and adhesion capabilities showed a complex relationship with DOPA substitution. Notably, the formulation containing 10% GelMA with high dopamine conjugation (HD) exhibited superior adhesion and mechanical strength. All formulations demonstrated shear-thinning behavior and recovery, making them suitable for injection and bioprinting applications. Although increased DOPA levels negatively affected crosslinking, the optimal formulation achieved a balance between adhesion and gel concentration. Rapid crosslinking was achieved within five minutes, enhancing the material’s suitability for clinical applications. In vitro cell-based assays confirmed the non-cytotoxic nature of the optimal adhesives, with metabolic activity showing significant increases over a 7-day period. These advancements support the development of improved tissue adhesives, potentially reducing reliance on sutures and enhancing wound healing outcomes.